“TECHNICALLY OPEN”: THE DEBATE OVER NATIVE AMERICAN RESERVED GROUNDWATER RIGHTS (Utah Environmental Law Review, 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} The challenge of providing water to all people in the arid Western states becomes increasingly more difficult as the population in these states continues to grow exponentially. Meanwhile, drought constantly threatens the already strained sources, forcing communities to confront the shortage through conservation efforts and mandated restrictions.   Even so, Native American tribes who have called this land home for hundreds of years seek to stake a claim in the fight for economically valuable water rights in the West.   Unfortunately, entering so late into the game of water appropriation means that less water is available since many sources are already fully appropriated.